Union and Industrial Community - Santistevan, Jorge (1972)
This paper addresses with the relationship between company unions and the industrial community, insofar as both figures represent the workers' collectivity. The author specifies the differences in the modality of creation, objectives, composition and their normative frameworks; highlighting that the will and obligatory nature in their conformation as a characteristic and distinctive element. Finally, the author emphasizes that their interests may coincide; however, the purpose of the figures is not to supplant or subtract participation from each other. In view of the above, the author emphasizes the importance of both figures acting in a coordinated manner to achieve their objectives.